PENGARUH PEMBERIAN E-BOOK TERHADAP PENGETAHUAN DAN KEPATUHAN IBU HAMIL TENTANG KONSUMSI TABLET FE - Densi Ernawati Br Sitohang; Lia Artika Sari; Herinawati Herinawati; Enny Susilawati (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2022)
The problem faced by the Indonesian government is the high prevalence of anemia in pregnant women. One of the factors causing anemia due to lack of iron intake in food consumed every day which is characterized by hemoglobin (Hb) levels below normal. This study aims to analyze the effect of giving e-books to the knowledge and adherence of pregnant women to consume FE tablets. This study uses a pre-experimental design that is one group pretest-posttest which was carried out at Pematang Rahim Village Assistant Health Center in March-July 2022 involving 31 pregnant women. The instruments used in this study were filling out questionnaires and observation sheets. The analysis used is univariate and bivariate analysis with statistical tests used to analyze the data for the two variables using T-test with a significance level of 5%. The results showed that the knowledge of pregnant women about Fe tablets before being given an e-book, most of the respondents had sufficient knowledge of 14 respondents (45.2%) and after being given the e-book most of the respondents had good knowledge of 20 respondents (64.5%) with P- values ​​< 0.05. The conclusion of the study is that there is a significant effect between the provision of e-books on the knowledge and compliance of pregnant women in consuming Fe tablets in the Working Area of ​​Pematang Rahim Village Assistant Health Center.